2000
DOI: 10.1093/jexbot/51.350.1515
|View full text |Cite
|
Sign up to set email alerts
|

Leaf development in Ricinus communis during drought stress: dynamics of growth processes, of cellular structure and of sink–source transition

Abstract: Dicot leaf growth is characterized by partly transient tip-to-base gradients of growth processes, structure and function. These gradients develop dynamically and interact with dynamically developing stress conditions like drought. In Ricinus communis plants growing under well-watered and drought conditions growth rates peaked during the late night and minimal values occurred in the late afternoon. During this diurnal course the leaf base always showed much higher rates than the leaf tip. The amplitude of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 51 publications
4
59
0
4
Order By: Relevance
“…It may have also been related to the increased leaf thickness and decreased leaf RWC induced by drought. The increased chlorophyll content under environmental stress has also been detected in some previous experiments (Schurr et al 2000;Renaut et al 2005). Additionally, we observed that shade increased the Chla and Chlb content in both populations.…”
Section: Discussionsupporting
confidence: 89%
“…It may have also been related to the increased leaf thickness and decreased leaf RWC induced by drought. The increased chlorophyll content under environmental stress has also been detected in some previous experiments (Schurr et al 2000;Renaut et al 2005). Additionally, we observed that shade increased the Chla and Chlb content in both populations.…”
Section: Discussionsupporting
confidence: 89%
“…However, in this study, regardless of RZ [CO 2 ] treatments, there were no differences in average root diameter at either 20˚C-RZT or A-RZT (Figure 1(D)). The temperature of a sink could affect its metabolic rate and thus its capacity to utilize carbohydrate [27]- [29]. Elevated RZ [CO 2 ] could also affect the physiological activities of roots and thus alter the pattern of photoassimilate partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…Os menores valores de altura de plantas e de diâmetro do caule nas condições mostradas nesse estudo sob baixos níveis de irrigação, provavelmente, ocorreram devido o fato do déficit hídrico provocar o fechamento dos estômatos, diminuindo a assimilação de CO 2 e, conseqüentemente, diminuindo as atividades fisiológicas das plantas, principalmente a divisão e o crescimento das células, refletindo assim em uma menor produtividade. Comentário semelhante fizeram Schurr et al (2000) e Rego et al (2004). Para a massa de 1000 aquênios (Figura 3) verificaram-se aumentos lineares em função do aumento das lâminas aplicadas, com efeito significativo (p < 0,05) e coeficientes de determinação de 0,977.…”
Section: Resultados E Discussõesunclassified